2014
DOI: 10.4103/2321-3868.130182
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for diagnosis, prophylaxis and treatment of invasive fungal infection post burn injury in China 2013

Abstract: Invasive fungal infection is one of the major complication of severe burns which can induce local or systemic inflammatory response and cause serious substantial damage to the patient. The incidence of fungal infection for burn victims is increasing dramatically during recent years. This guideline, organized by Chinese Society of Burn Surgeons, aims to standardize the diagnosis, prevention and treatment of burn invasive fungal infection. It can be used as one of the tools for treatment of major burn patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Furthermore, the treatment guidelines include infectious source control, rational use of antibiotics, continuous blood purification, application of glucocorticoids, immunomodulation, symptomatic and supportive treatment, and prevention of hospital-acquired infection. For burn invasive fungal infections, experts from the IBR and other 18 burn centers all over China composed the “Guideline for diagnosis, prophylaxis and treatment of invasive fungal infection post burn injury in China 2013” [ 32 ]. Host susceptibility, clinical manifestation, standardization of diagnosis, prevention, and treatment of fungal infection including surgical intervention are embodied.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the treatment guidelines include infectious source control, rational use of antibiotics, continuous blood purification, application of glucocorticoids, immunomodulation, symptomatic and supportive treatment, and prevention of hospital-acquired infection. For burn invasive fungal infections, experts from the IBR and other 18 burn centers all over China composed the “Guideline for diagnosis, prophylaxis and treatment of invasive fungal infection post burn injury in China 2013” [ 32 ]. Host susceptibility, clinical manifestation, standardization of diagnosis, prevention, and treatment of fungal infection including surgical intervention are embodied.…”
Section: Reviewmentioning
confidence: 99%
“…This increase has been attributed to the human immunodeficiency virus (HIV) pandemic, medical and oncological therapeutic advances and the presence of better diagnostics for IFIs [ 2 ]. Other identified risk factors for IFI include malnutrition, severe burns, systemic corticosteroids for > 7 days, diabetes mellitus and multiple major surgery [ 3 , 4 ]. However the high morbidity and mortality from IFIs has been linked to delayed diagnosis and treatment, the development of resistance and the severity of illness [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Chinese large-scale, observational study of antifungal therapy in hematological diseases revealed that in 1401 patients undergoing hematopoietic stem cell transplantation (HSCT), the most common medications for invasive fungal diseases were triazoles (mainly fluconazole) and echinocandins [ 16 ] and a Chinese guideline for treatment of invasive fungal infection after burn injury recommends azoles and candins as first-line treatment for empirical therapies and excludes polyenes for prophylaxis [ 17 ]. Another guideline for the management of candidiasis from the Infectious Diseases Society of America (IDSA) recommends caspofungin and azoles as first-line treatments when azole resistance is unlikely [ 18 ].…”
Section: Introductionmentioning
confidence: 99%